2017
DOI: 10.1016/j.je.2016.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of overdose episodes from the period prior to hospitalization for drug poisoning until discharge in Japan: An exploratory descriptive study using a nationwide claims database

Abstract: BackgroundLittle is known about the nationwide epidemiology of the annual rate, causative substance, and clinical course of overdose-related admission. We aimed to describe the epidemiology of overdose episodes from the period prior to hospitalization for drug poisoning until discharge to home.MethodsWe assessed all cases of admission due to overdose (21,663 episodes) in Japan from October 2012 through September 2013 using the National Database of Health Insurance Claims and Specific Health Checkups of Japan.R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 30 publications
2
45
0
Order By: Relevance
“…Since 2011, it has been possible for researchers to use the NDB for identifying accurate evidence on which promotion of policies may be based, with the aim of improving the quality of medical services, or for conducting analysis and research that are useful for these policies, and for advancing academic research. The NDB covers almost all patients who have received medical care services under the universal health insurance system, but does not include medical services that are not covered under this system . We used datasets from a policy research group's study entitled ‘Policy research for promoting functional reinforcement of the psychiatric care provision system’ to extract data in line with our objectives and to create a separate dataset for our retrospective study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since 2011, it has been possible for researchers to use the NDB for identifying accurate evidence on which promotion of policies may be based, with the aim of improving the quality of medical services, or for conducting analysis and research that are useful for these policies, and for advancing academic research. The NDB covers almost all patients who have received medical care services under the universal health insurance system, but does not include medical services that are not covered under this system . We used datasets from a policy research group's study entitled ‘Policy research for promoting functional reinforcement of the psychiatric care provision system’ to extract data in line with our objectives and to create a separate dataset for our retrospective study.…”
Section: Methodsmentioning
confidence: 99%
“…The NDB covers almost all patients who have received medical care services under the universal health insurance system, but does not include medical services that are not covered under this system. 22 We used datasets from a policy research group's study entitled 'Policy research for promoting functional reinforcement of the psychiatric care provision system' to extract data in line with our objectives and to create a separate dataset for our retrospective study.…”
Section: Data Sourcementioning
confidence: 99%
“…This was a retrospective observational cohort study carried out using data from the National Database of Health Insurance Claims in Japan. The details of this database have been described elsewhere. Briefly, it is an all‐patient administrative claims database developed by Japan's Ministry of Health, Labour and Welfare that covers more than 126 million people and 1·9 billion claims annually.…”
Section: Methodsmentioning
confidence: 99%
“…Drug poisoning or overdosing, whether accidental or intentional, is a major cause of comorbidity and mortality worldwide. In Japan, it is reported that >20,000 people are admitted to hospitals because of drug poisoning annually . It is reportedly the major cause of emergency admissions in Japan, the USA, and other countries…”
Section: Introductionmentioning
confidence: 99%